Self-Compassion dan Help-Seeking Intention pada Mahasiswa - Ahmad Kholiqul Khoir (Universitas Negeri Makassar, 2023)
ABSTRACTStudents are individuals who are susceptible to mental disorders; therefore, they need to seek help in order to address the mental disorders they experience. However, students often lack the intention to seek help when they encounter mental disorders. This study aims to investigate the relationship between self-compassion and the intention to seek help among students.. The research hypothesis posits a positive correlation between self-compassion and the intention to seek help among college students. The research methodology adopts a correlational quantitative approach, and data is collected using a convenience sampling method. The participants in this study consist of 105 male and female Universitas Islam Indonesia students aged between 17 and 25. The measurement instruments employed include the General Help-Seeking Questionnaire (GHSQ) for assessing help-seeking intention, and the Self-Compassion Scale (SCS) to measure self-compassion. The collected data is then subjected to correlation analysis using the Spearman Rho method. The results of the correlation analysis indicate a positive relationship between self-compassion and help-seeking intention among college students, with a significance value (p) of 0.016 and a correlation coefficient (r) of 0.209. Consequently, higher levels of self-compassion are associated with a greater intention to seek help among the participants, and vice versa.Keywords: Self-Compassion, Help-Seeking Intention, College Student. ABSTRAKMahasiswa adalah subjek yang rentan terkena gangguan mental. Oleh karena itu, mahasiswa perlu mencari bantuan agar gangguan mental yang dialami dapat terselesaikan. Namun, mahasiswa cenderung tidak berniat mencari bantuan saat mengalami gangguan mental. Penelitian ini bertujuan untuk mengetahui hubungan antara self-compassion dan help-seeking intention pada mahasiswa. Adapun hipotesis penelitian adalah terdapat hubungan positif antara self-compassion dan help-seeking intention pada mahasiswa. Metode penelitian menggunakan pendekatan kuantitatif korelasional, dan dalam mengambil data memakai metode convenience sampling. Subjek dalam penelitian ini sejumlah 105 mahasiswa Universitas Islam Indonesia laki-laki dan perempuan dengan rentang usia 17-25. Alat ukur yang dipakai adalah General Help-Seeking Questionnaire (GHSQ) untuk mengukur help-seeking intention dan Skala Welas Diri untuk mengukur self-compassion. Kemudian, uji korelasi memakai Spearman Rho. Hasil uji korelasi menunjukkan bahwa terdapat hubungan positif antara self-compassion dan help-seeking intention pada mahasiswa dengan nilai signifikansi (p)=0.016 dan koefisien korelasi (r) 0.209. Berdasarkan ini maka semakin tinggi self-compassion maka semakin tinggi pula help-seeking intention subjek, begitu sebaliknya.Kata Kunci: Welas Diri, Intensi Mencari Bantuan, Mahasiswa.